Issues and challenges in managing curriculum change in primary schools: A case study of managing Year Four History Curriculum in the District of Kuala Selangor, Malaysia - Paramasivam, Thangamalar; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The case study aimed to explore and explain the issues and challenges experienced in the management of curriculum change in primary schools. This was done by analysing the management of curriculum change brought about by the introduction the History curriculum for the Year Four Primary Schools Standard based Curriculum. This case study used a descriptive- interpretative approach grounded in the qualitative research tradition. Precisely, it is an instrumental case study. Data was collected through analysis of documents, in-depth interviewing (based on semi-structured interviews) and the direct observations of learning and teaching of History lessons. It was located within the context of eight selected schools (four National Primary Schools and four Tamil Type National Primary schools). A total of twenty eight respondents were interviewed. The findings show that the respondents did face issues and challenges in managing the Year Four History curriculum. They were pertaining to curriculum content, teaching and learning process, assessment, availability and utilization of time, training and staff development, physical facilities. The findings of this study can assist curriculum developers, curriculum administrators, school management team and teachers in managing the Year Four History curriculum. They were pertaining to curriculum content, teaching and learning process, assessment, availability and utilization of time, training and staff development, physical facilities. The findings of this study can assist curriculum developers, curriculum administrators, school management team and teachers in improving quality of primary school curriculum change management.